2013
DOI: 10.1007/s11259-013-9570-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the epidemiological behavior of mastitis pathogens by applying time-series analysis in results of milk samples submitted for microbiological examination

Abstract: The objective of this study is to examine and compare the trends of mastitis pathogens in quarter milk samples (n = 240,232) submitted for microbiological examination at the Milk Analysis Laboratory (L.I.G.A.L.) at Galicia, Spain from June 2005 to September 2011. Autoregressive Integrated Moving Average (ARIMA) models and multivariate statistical techniques such as Cluster Analysis were used in order to detect seasonal trends and similarities between the series trends and to classify mastitis pathogens into re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
2
5
0
Order By: Relevance
“…Contagious pathogens generally spread from cow to cow with the infected udder being the primary source of infection whereas environmental pathogens, which are found in the environment where the cow resides, spread directly to the udder from the environment [ 2 ]. Staphylococcus aureus , a major mastitis pathogen is commonly considered a contagious pathogen, although recently it has been recognized that its epidemiological behaviour is not clear cut, with strains demonstrating contagious and/or environmental transmission patterns [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Contagious pathogens generally spread from cow to cow with the infected udder being the primary source of infection whereas environmental pathogens, which are found in the environment where the cow resides, spread directly to the udder from the environment [ 2 ]. Staphylococcus aureus , a major mastitis pathogen is commonly considered a contagious pathogen, although recently it has been recognized that its epidemiological behaviour is not clear cut, with strains demonstrating contagious and/or environmental transmission patterns [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that chronic mastitis is the only condition for which the predictor trained on the reduced data set yielded a higher sensitivity than the one trained on the full data set. Two of the four existing studies on the application of ML algorithms to mastitis phenomenology 30, 31 do not predict disease incidence and a direct comparison with our approach is not possible. The other two approaches outperform our approach with sensitivities of >93% 33 and 97.7% 32 respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The literature on the prediction of diseases is frequently based on black-box sensor systems in which prediction algorithms are used that are of commercial interest and not publicly known or evaluated 26 or the reported sensitivity and specificity of prediction algorithms varies widely 9 . Diseases for which successful applications of ML approaches have been reported include lameness [27][28][29] , mastitis [30][31][32][33] , metabolic status, i.e. ketosis (hyperketonemia) and periparturient hypocalcemia (milk fever) [34][35][36][37][38] , infectious diseases 39,40 and oestrus detection 41 .…”
Section: Introductionmentioning
confidence: 99%
“…Detecting diseases, such as mastitis, early would favor both economics and the cow’s welfare. Autoregressive integrated moving average models and CA were able to detect seasonal trends of mastitis pathogens in quarter milk samples, which are regularly assessed for microbial examination [ 52 ]. These classification models further detected that mastitis pathogens can be classified into both contagious and environmental categories, whereas previously, it has been reported that they could only be either one or the other [ 52 ].…”
Section: Resultsmentioning
confidence: 99%